The determinants and consequences of forgoing healthcare. (30th September 2020) - Petrovic, D; Sandoval, J L; Guessous, I; Stringhini, S
Abstract: Background: Forgoing healthcare is associated with unfavorable health-related outcomes, a higher risk of hospitalization, and a decreased quality of life. Relatively to its neighboring countries, forgoing healthcare for economic reasons is high in Switzerland, primarily because of the high out of pocket expenditures that characterize the Swiss healthcare system. The purpose of this study was to investigate the determinants of forgoing healthcare, and to examine the long term health-related consequences of unmet medical needs. Methods: We used data from "Bus Santé", a cross-sectional study conducted in the city of Geneva (CH). Socioeconomic factors were self-reported by participants at baseline (N = 5032, 2007-2011), including income, education, receiving subsidies, and insurance deductibles (mandatory out of pocket expenditures). Forgoing healthcare for economic reasons was self-reported by study participants, including details about the frequency and the type of forgone care. Prospectively, a subset of participants came for a follow-up visit (2014-2015) in order to assess objective (glycemia, blood pressure, plasma lipids) and subjective health-outcomes (self-reported physical and mental health) resulting from forgone healthcare at baseline. Results: At baseline, adverse socioeconomic circumstances (lower income, education, receiving subsidies, and high deductibles) were associated with a higher risk of forgoing healthcare (OR range 1.51-5.49, p < 0.015). Four years later, participants who reported forgoing healthcare at baseline were at a higher risk of having lower HDL-cholesterol (β=-0.08 [-0.14;-0.03]), and adverse physical and mental self-reported health outcomes when compared to controls (p < 0.017). Conclusions: Forgoing healthcare is driven by adverse socioeconomic circumstances, subsequently leading to adverse lipid profiles and poor self-reported health outcomes. Unmet medical needs may constitute a pathway through which socioeconomic status affects health. Key messages: Adverse socioeconomic circumstances lead to unmet medical needs, even in wealthy countries. Unmet medical needs lead to poor objective and subjective health-related outcomes.